Aldehyde-removing inorganic artificial stone and preparation method thereof
By using photocatalyst nanotitanium dioxide and other raw materials in inorganic artificial stones, an aldehyde removal material that can efficiently degrade formaldehyde under natural light is solved, and the problems of low formaldehyde removal efficiency, short material life and environmental pollution in the prior art are solved, and high efficiency is achieved , long-lasting and environmentally friendly indoor air purification effect.
Patent Information
- Application Number
- CN202411207457.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing interior decoration materials are inefficient in removing formaldehyde, have short service life, may cause secondary pollution, and are not effective in dull or low-light environments, and there are waste of resources and environmental pollution problems in the production process.
Photocatalyst nanotitanium dioxide is used as a photocatalyst, combined with cement, construction solid waste, industrial tailings and other raw materials, and is molded through single-piece vacuum high-frequency vibration compression to form inorganic artificial stones that can effectively degrade formaldehyde under natural light, with a removal rate of 90. %above.
It significantly improves indoor air quality, has high durability and low cost, and is suitable for a variety of indoor environments. The production process is simple and easy to scale, reducing environmental pollution.
Smart Images

Figure CN119263706A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of artificial stone preparation, and in particular to a formaldehyde-removing inorganic artificial stone and a preparation method thereof. Background Art
[0002] With the improvement of modern living standards, people are paying more and more attention to the comfort and health of their living environment. The choice of interior decoration materials is not only related to aesthetics and practicality, but also directly affects the health of residents. Formaldehyde, as a common indoor air pollutant, mainly comes from decoration materials such as furniture, flooring, and paint. Its release cycle can last for several years, posing a serious threat to human health. Therefore, the development of interior decoration materials that can effectively remove formaldehyde has become an important research direction in the building materials industry.
[0003] At present, some indoor decoration materials with formaldehyde removal functions have appeared on the market, such as activated carbon, photocatalyst coatings, etc. These materials remove formaldehyde by adsorption or catalytic degradation, and have achieved certain results. However, the formaldehyde removal efficiency of most existing materials is limited, and they often have problems such as short service life, easy saturation, and need for regular replacement. In addition, some materials may produce secondary pollution during the formaldehyde removal process, or the formaldehyde removal effect is greatly reduced under certain conditions (such as lightless environment).
[0004] The shortcomings of the existing technology are mainly reflected in the following aspects: 1) The formaldehyde removal efficiency is not high, and it is difficult to significantly reduce the indoor formaldehyde concentration in a short period of time; 2) The durability and stability of the materials are insufficient, and they need to be replaced frequently, which increases the cost of use and the difficulty of maintenance; 3) The formaldehyde removal effect of some materials is limited in lightless or low-light environments, which limits their application in a variety of indoor environments; 4) Existing materials may have problems of resource waste and environmental pollution in the production process, which is inconsistent with the concept of green and sustainable development. Summary of the invention
[0005] In view of the above defects or improvement needs of the prior art, the purpose of the present invention is to provide a formaldehyde-removing inorganic artificial stone and a preparation method thereof. By adding photocatalyst nano-titanium dioxide, formaldehyde can be effectively degraded under the action of natural light, and the removal rate reaches more than 90%, significantly improving the indoor air quality; the manufacturing process of the present invention is very simple and easy to implement, and the formaldehyde degradation rate of more than 90% can be achieved with a low dosage of photocatalyst. The overall manufacturing cost is not high, and a high efficiency of formaldehyde degradation rate can be obtained; in addition, the preparation process is simple and easy to scale up. Through single-piece vacuum high-frequency vibration pressing and molding, the production efficiency and the density of the board can be improved.
[0006] In the first aspect, the present invention provides a formaldehyde-removing inorganic artificial stone, comprising the following raw materials in parts by weight: 20 to 30 parts of cement, 5 to 15 parts of auxiliary cementitious materials, 40 to 50 parts of construction solid waste, 10 to 20 parts of industrial tailings, 1 to 2 parts of photocatalyst, 2 to 4 parts of activated alumina, 1 to 3 parts of zeolite powder, 1 to 2 parts of water reducer, 1 to 2 parts of water, and 3 to 6 parts of toughening agent; by adopting a preparation method of photocatalyst nano titanium dioxide monolithic vacuum high-frequency vibration molding, the strength, toughness and formaldehyde degradation rate of the inorganic artificial stone can be effectively improved.
[0007] Furthermore, the construction solid waste is recycled concrete after crushing and screening, and the particle size range and proportion include: 10 to 16 parts of 9.5 to 16 mm, 8 to 12 parts of 4.75 to 9.5 mm, 5 to 10 parts of 2.36 to 4.75 mm, 5 to 10 parts of 0.075 to 2.36 mm, and 5 to 10 parts of 0 to 0.075 mm.
[0008] Furthermore, the industrial tailings include one of copper tailings, lithium tailings or tungsten tailings, and the particle size range and proportion of the industrial tailings include: 5 to 10 parts of 0.075 to 2.36 mm particle size and 10 to 15 parts of 0 to 0.075 mm particle size.
[0009] Furthermore, the photocatalyst comprises nano titanium dioxide with a particle size of 20 to 50 nm.
[0010] Furthermore, the specific surface area of the activated alumina is 200 to 300 m 2 / g, and the pore diameter of the zeolite powder is 0.3-1 nm.
[0011] Furthermore, the auxiliary cementitious material includes one of metakaolin and bentonite; the water reducer includes a polycarboxylic acid water reducer; and the toughening agent includes one of styrene-butadiene emulsion and styrene-acrylic emulsion.
[0012] In a second aspect, the present invention provides a method for preparing formaldehyde-removing inorganic artificial stone, comprising:
[0013] S100, uniformly dispersing the photocatalyst nano-titanium dioxide in water using an ultrasonic disperser to obtain a photocatalyst nano-titanium dioxide dispersion;
[0014] S200, putting artificial stone aggregate, zeolite powder, activated alumina and filler into a high-speed mixer for dry mixing, then adding the photocatalyst nano titanium dioxide dispersion and admixtures for wet mixing, adding cement and auxiliary cementitious materials and continuing to stir, and finally adding toughening agent and continuing to stir, and after the stirring is completed, obtaining an artificial stone mixture with uniform moisture and characteristics suitable for compression molding;
[0015] S300, laying a PET film on the bottom of the molding mold, evenly spreading the artificial stone mixture on the PET film, placing it in a molding device and pressing the rough board under high-frequency vibration in a vacuum state;
[0016] S400, placing the rough board into a mold and sending it into a curing box for primary curing, demoulding after the curing is completed, and continuing secondary curing after the demoulding is completed to ensure that the cement-based board is fully reacted and cured to reach a processable degree;
[0017] S500, performing a finishing process to obtain the final formaldehyde-free inorganic artificial stone.
[0018] Furthermore, the total stirring time in step S200 is 5 to 10 minutes.
[0019] Furthermore, in the step S300, the vacuum degree of the pressing molding is -0.095 MPa, the holding time is 120 to 180 seconds, and the pressure is 12 to 16 MPa.
[0020] Furthermore, the primary curing time is 24 hours, the temperature is 20-40° C., and the humidity is ≥95%, and the secondary curing time is 14-28 days, and the other conditions are the same.
[0021] Beneficial effects of the present invention:
[0022] 1. The present invention can effectively degrade formaldehyde under the action of natural light by adding photocatalyst nano titanium dioxide, with a removal rate of more than 90%, significantly improving indoor air quality; the manufacturing process of the present invention is very simple and easy to implement, and the formaldehyde degradation rate of more than 90% can be achieved with a low dosage of the photocatalyst, the overall manufacturing cost is not high, and a high efficiency of formaldehyde degradation rate can be obtained; in addition, the preparation process is simple and easy to scale production, and the production efficiency and the density of the board can be improved by single-piece vacuum high-frequency vibration pressing and molding.
[0023] 2. The present invention utilizes construction solid waste and industrial tailings as raw materials, which reduces pollution to the environment, reduces the cost of raw materials, and promotes the recycling of building materials.
[0024] 3. The stability of the photocatalyst in the present invention ensures that the plate has a lasting formaldehyde removal effect and is suitable for long-term improvement of the air quality in indoor environments.
[0025] 4. The present invention is applicable to various indoor environments such as homes, hospitals, and schools, and can meet the needs of different scenarios for healthy indoor air.
[0026] 5. The board prepared by the present invention can be easily subjected to finishing processes such as thickness determination, grinding, and polishing to meet diverse decoration and design requirements.
[0027] Additional aspects and advantages of the present application will be partially given in the following description, which will become apparent from the following description, or will be understood through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0029] Figure 1 This is a brief flow chart of a method for preparing formaldehyde-removing inorganic artificial stone in an embodiment of the present invention;
[0030] Figure 2 It is a specific flow chart of a method for preparing formaldehyde-removing inorganic artificial stone in an embodiment of the present invention. DETAILED DESCRIPTION
[0031] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. It is to be understood that the specific embodiments described herein are only used to explain the present invention, rather than to limit the present invention. It should also be noted that, for ease of description, only parts related to the present invention, rather than all structures, are shown in the accompanying drawings.
[0032] Those skilled in the art will appreciate that, unless otherwise stated, the singular forms "a", "an", "said" and "the" used herein may also include plural forms. It should be further understood that the term "comprising" used in the specification of the present application refers to the presence of the features, integers, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.
[0033] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical terms and scientific terms) used herein have the same meaning as the general understanding of those skilled in the art to which this application belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have the same meaning as in the context of the prior art, and will not be interpreted with an idealized or overly formal meaning unless specifically defined as in the embodiments of this application.
[0034] The invention provides an inorganic artificial stone for removing formaldehyde and a preparation method thereof. By adding photocatalyst nano titanium dioxide, formaldehyde can be effectively degraded under the action of natural light, and the removal rate reaches more than 90%, thereby significantly improving indoor air quality. The manufacturing process of the invention is very simple and easy to implement, and the formaldehyde degradation rate of more than 90% can be achieved with a low dosage of the photocatalyst, the overall manufacturing cost is not high, and a high-efficiency formaldehyde degradation rate can be obtained. In addition, the preparation process is simple and easy to mass produce, and the production efficiency and the density of the plate can be improved by single-piece vacuum high-frequency vibration pressing and molding.
[0035] like Figure 1 Figure 2 As shown, the present invention provides a method for preparing formaldehyde-removing inorganic artificial stone, comprising:
[0036] S100. Check that all equipment is operating normally and that the raw materials meet the requirements, pre-treat the raw materials in a certain way, and prepare pre-treated cement, auxiliary cementitious materials, construction solid waste, industrial tailings, photocatalyst, activated alumina, zeolite powder, water reducer, water and toughening agent according to the formula ratio;
[0037] S200, use ultrasonic disperser to evenly disperse photocatalyst nano titanium dioxide in water to form a stable suspension. This step is crucial because the uniform dispersion of photocatalyst directly affects the formaldehyde removal effect of the final product.
[0038] S300, put artificial stone aggregate, zeolite powder, activated alumina and filler into a high-speed mixer for dry mixing. After dry mixing, add photocatalyst nano titanium dioxide dispersion and water reducer for wet mixing. Subsequently, add cement and auxiliary cementitious materials and continue to stir until a uniform mixture is formed. Finally, add toughening agent for the final stirring to ensure that the material has uniform moisture and reaches the characteristics suitable for compression molding.
[0039] S400, spread a PET film on the bottom of the molding die, and evenly spread the mixture on the PET film. Place the mold in the molding equipment, and perform high-frequency vibration pressing and molding under vacuum. During the pressing process, the vacuum degree is -0.095MPa, the press holding time is 120 to 180 seconds, and the press pressure is 12 to 16MPa.
[0040] S500, the formed artificial stone board is sent to the curing box for primary curing, and cured for 24 hours in an environment with a temperature of 20-40℃ and a humidity of ≥95%. After the primary curing is completed, demoulding is carried out, and then secondary curing is carried out to ensure that the cement-based board is fully reacted and cured.
[0041] S600, after the maintenance is completed, the finishing process is carried out, including thickness determination, grinding, polishing and protection, to meet the needs of different application scenarios.
[0042] The total stirring time in step S200 is 5 to 10 minutes. The first curing time is 24 hours, the temperature is 20 to 40° C., the humidity is ≥ 95%, and the second curing time is 14 to 28 days, and the other conditions are the same.
[0043] The present invention provides a formaldehyde-removing inorganic artificial stone, which is prepared according to the above-mentioned preparation method of formaldehyde-removing inorganic artificial stone, and comprises the following raw materials in parts by weight:
[0044] 20-30 parts of cement, as the main cementitious material, provides basic strength and stability; 5-15 parts of auxiliary cementitious materials, such as kaolin or bentonite, are used to enhance adhesion and improve material properties; 40-50 parts of construction solid waste, such as recycled concrete, are used to achieve resource recycling; 10-20 parts of industrial tailings, such as copper tailings, lithium tailings or tungsten tailings, with a total ratio of 10-20 parts, are used to further enhance material properties and achieve waste utilization; 1-2 parts of photocatalyst, nano-titanium dioxide, is used to catalytically degrade formaldehyde under light; 2-4 parts of activated alumina, as a gas adsorbent, is used to enhance the adsorption effect; 1-3 parts of zeolite powder, which has a specific pore size and is used to adsorb and fix harmful gases; 1-2 parts of water reducer, polycarboxylic acid water reducer, is used to improve the processability of the material; 1-2 parts of water, as a necessary medium for mixing and molding; 3-6 parts of toughening agent, such as styrene-butadiene emulsion or styrene-acrylic emulsion, is used to improve the toughness of the material.
[0045] The construction solid waste is recycled concrete after crushing and screening, and the particle size range and proportion include: 10 to 16 parts of 9.5 to 16 mm, 8 to 12 parts of 4.75 to 9.5 mm, 5 to 10 parts of 2.36 to 4.75 mm, 5 to 10 parts of 0.075 to 2.36 mm, and 5 to 10 parts of 0 to 0.075 mm. The industrial tailings include one of copper tailings, lithium tailings or tungsten tailings, and the particle size range and proportion of the industrial tailings include: 5 to 10 parts of 0.075 to 2.36 mm and 10 to 15 parts of 0 to 0.075 mm. The photocatalyst includes nano titanium dioxide with a particle size of 20 to 50 nm. The specific surface area of the activated alumina is 200 to 300 m 2 / g, the pore size of the zeolite powder is 0.3-1nm. The auxiliary gelling material includes one of metakaolin or bentonite; the water reducer includes a polycarboxylic acid water reducer; the toughening agent includes one of styrene-butadiene emulsion or styrene-acrylic emulsion.
[0046] The present invention can effectively degrade formaldehyde under the action of natural light by adding photocatalyst nano titanium dioxide, with a removal rate of more than 90%, significantly improving indoor air quality; the manufacturing process of the present invention is very simple and easy to implement, and the formaldehyde degradation rate of more than 90% can be achieved with a low dosage of photocatalyst, the overall manufacturing cost is not high, and a high-efficiency formaldehyde degradation rate can be obtained; in addition, the preparation process is simple and easy to scale production, and the production efficiency and the density of the plate can be improved by single-piece vacuum high-frequency vibration pressing and molding. In addition, the present invention uses construction solid waste and industrial tailings in the preparation process, and the impact on the environment is evaluated. By reducing dependence on natural resources, the present invention helps to reduce the impact of mining and waste treatment on the environment and realize the green production of building materials.
[0047] The present invention provides three embodiments and two comparative examples and conducts performance tests to test the blank test chamber pollutant concentration value, sample test chamber pollutant concentration value and removal rate of formaldehyde in the comparative examples and the embodiments, as follows:
[0048] Example 1
[0049] The embodiment of the present invention provides a formaldehyde-removing inorganic artificial stone, comprising the following preparation steps:
[0050] S100. Check that all equipment is operating normally and the raw materials meet the requirements. Pre-treat the raw materials in a certain way and prepare 1 part of pre-treated photocatalyst nano-titanium dioxide, 2 parts of activated alumina, 1 part of zeolite powder, 25 parts of cement, 10 parts of auxiliary gel material, 45 parts of construction solid waste, 15 parts of industrial tailings, 1 part of water reducer, 1 part of water and 4 parts of toughening agent according to the formula ratio.
[0051] S200, use ultrasonic disperser to evenly disperse photocatalyst nano titanium dioxide in water to form a stable suspension. This step is crucial because the uniform dispersion of photocatalyst directly affects the formaldehyde removal effect of the final product.
[0052] S300, put artificial stone aggregate, zeolite powder, activated alumina and filler into a high-speed mixer for dry mixing. After dry mixing, add photocatalyst nano titanium dioxide dispersion and water reducer for wet mixing. Subsequently, add cement and auxiliary cementitious materials and continue to stir until a uniform mixture is formed. Finally, add toughening agent for the final stirring to ensure that the material has uniform moisture and reaches the characteristics suitable for compression molding.
[0053] S400, spread a PET film on the bottom of the molding die, and evenly spread the mixture on the PET film. Place the mold in the molding equipment, and perform high-frequency vibration pressing and molding under vacuum. During the pressing process, the vacuum degree is -0.095MPa, the press holding time is 120 to 180 seconds, and the press pressure is 12 to 16MPa.
[0054] S500, the formed artificial stone board is sent to the curing box for primary curing, and cured for 24 hours in an environment with a temperature of 20-40℃ and a humidity of ≥95%. After the primary curing is completed, demoulding is carried out, and then secondary curing is carried out to ensure that the cement-based board is fully reacted and cured.
[0055] S600, after the maintenance is completed, the finishing process is carried out, including thickness determination, grinding, polishing and protection, to meet the needs of different application scenarios.
[0056] Example 2
[0057] The embodiment of the present invention provides a formaldehyde-removing inorganic artificial stone, comprising the following preparation steps:
[0058] S100. Check that all equipment is operating normally and the raw materials meet the requirements. Pre-treat the raw materials in a certain way and prepare 2 parts of pre-treated photocatalyst nano-titanium dioxide, 2 parts of activated alumina, 1 part of zeolite powder, 25 parts of cement, 10 parts of auxiliary gel materials, 45 parts of construction solid waste, 15 parts of industrial tailings, 1 part of water reducer, 1 part of water and 4 parts of toughening agent according to the formula ratio.
[0059] S200, use an ultrasonic disperser to evenly disperse the photocatalyst nano titanium dioxide in water to form a stable suspension. This step is crucial because the uniform dispersion of the photocatalyst directly affects the formaldehyde removal effect of the final product.
[0060] S300, put artificial stone aggregate, zeolite powder, activated alumina and filler into a high-speed mixer for dry mixing. After dry mixing, add photocatalyst nano titanium dioxide dispersion and water reducer for wet mixing. Subsequently, add cement and auxiliary cementitious materials and continue to stir until a uniform mixture is formed. Finally, add toughening agent for the final stirring to ensure that the material has uniform moisture and reaches the characteristics suitable for compression molding.
[0061] S400, spread a PET film on the bottom of the molding die, and evenly spread the mixture on the PET film. Place the mold in the molding equipment, and perform high-frequency vibration pressing and molding under vacuum. During the pressing process, the vacuum degree is -0.095MPa, the press holding time is 120 to 180 seconds, and the press pressure is 12 to 16MPa.
[0062] S500, the formed artificial stone board is sent to the curing box for primary curing, and cured for 24 hours in an environment with a temperature of 20-40℃ and a humidity of ≥95%. After the primary curing is completed, demoulding is carried out, and then secondary curing is carried out to ensure that the cement-based board is fully reacted and cured.
[0063] S600, after the maintenance is completed, the finishing process is carried out, including thickness determination, grinding, polishing and protection, to meet the needs of different application scenarios.
[0064] Example 3
[0065] The embodiment of the present invention provides a formaldehyde-removing inorganic artificial stone, comprising the following preparation steps:
[0066] S100. Check that all equipment is operating normally and the raw materials meet the requirements. Pre-treat the raw materials in a certain way and prepare 2 parts of pre-treated photocatalyst nano-titanium dioxide, 4 parts of activated alumina, 3 parts of zeolite powder, 25 parts of cement, 10 parts of auxiliary gel materials, 45 parts of construction solid waste, 15 parts of industrial tailings, 1 part of water reducer, 1 part of water and 4 parts of toughening agent according to the formula ratio.
[0067] S200, use an ultrasonic disperser to evenly disperse the photocatalyst nano titanium dioxide in water to form a stable suspension. This step is crucial because the uniform dispersion of the photocatalyst directly affects the formaldehyde removal effect of the final product.
[0068] S300, put artificial stone aggregate, zeolite powder, activated alumina and filler into a high-speed mixer for dry mixing. After dry mixing, add photocatalyst nano titanium dioxide dispersion and water reducer for wet mixing. Subsequently, add cement and auxiliary cementitious materials and continue to stir until a uniform mixture is formed. Finally, add toughening agent for the final stirring to ensure that the material has uniform moisture and reaches the characteristics suitable for compression molding.
[0069] S400, spread a PET film on the bottom of the molding die, and evenly spread the mixture on the PET film. Place the mold in the molding equipment, and perform high-frequency vibration pressing and molding under vacuum. During the pressing process, the vacuum degree is -0.095MPa, the press holding time is 120 to 180 seconds, and the press pressure is 12 to 16MPa.
[0070] S500, the formed artificial stone board is sent to the curing box for primary curing, and cured for 24 hours in an environment with a temperature of 20-40℃ and a humidity of ≥95%. After the primary curing is completed, demoulding is carried out, and then secondary curing is carried out to ensure that the cement-based board is fully reacted and cured.
[0071] S600, after maintenance, the finishing process is carried out, including thickness determination, grinding, polishing and protection, to meet the needs of different application scenarios.
[0072] Comparative Example 1
[0073] The embodiment of the present invention provides a formaldehyde-removing inorganic artificial stone, comprising the following preparation steps:
[0074] S100. Check that all equipment is operating normally and the raw materials meet the requirements, pre-treat the raw materials in a certain way, and prepare 0 parts of pre-treated photocatalyst nano-titanium dioxide, 4 parts of activated alumina, 3 parts of the zeolite powder, 25 parts of cement, 10 parts of auxiliary gel material, 45 parts of construction solid waste, 15 parts of industrial tailings, 1 part of water reducer, 1 part of water and 4 parts of toughening agent according to the formula ratio.
[0075] S200, use an ultrasonic disperser to evenly disperse the photocatalyst nano titanium dioxide in water to form a stable suspension. This step is crucial because the uniform dispersion of the photocatalyst directly affects the formaldehyde removal effect of the final product.
[0076] S300, put artificial stone aggregate, zeolite powder, activated alumina and filler into a high-speed mixer for dry mixing. After dry mixing, add photocatalyst nano titanium dioxide dispersion and water reducer for wet mixing. Subsequently, add cement and auxiliary cementitious materials and continue to stir until a uniform mixture is formed. Finally, add toughening agent for the final stirring to ensure that the material has uniform moisture and reaches the characteristics suitable for compression molding.
[0077] S400, spread a PET film on the bottom of the molding die, and evenly spread the mixture on the PET film. Place the mold in the molding equipment, and perform high-frequency vibration pressing and molding under vacuum. During the pressing process, the vacuum degree is -0.095MPa, the press holding time is 120 to 180 seconds, and the press pressure is 12 to 16MPa.
[0078] S500, the formed artificial stone board is sent to the curing box for primary curing, and cured for 24 hours in an environment with a temperature of 20-40℃ and a humidity of ≥95%. After the primary curing is completed, demoulding is carried out, and then secondary curing is carried out to ensure that the cement-based board is fully reacted and cured.
[0079] S600, after maintenance, the finishing process is carried out, including thickness determination, grinding, polishing and protection, to meet the needs of different application scenarios.
[0080] Comparative Example 2
[0081] The embodiment of the present invention provides a formaldehyde-removing inorganic artificial stone, comprising the following preparation steps:
[0082] S100. Check that all equipment is operating normally and the raw materials meet the requirements, pre-treat the raw materials in a certain way, and prepare 2 parts of pre-treated photocatalyst nano-titanium dioxide, 0 parts of activated alumina, 0 parts of the zeolite powder, 25 parts of cement, 10 parts of auxiliary gel materials, 45 parts of construction solid waste, 15 parts of industrial tailings, 1 part of water reducer, 1 part of water and 4 parts of toughening agent according to the formula ratio.
[0083] S200, use an ultrasonic disperser to evenly disperse the photocatalyst nano titanium dioxide in water to form a stable suspension. This step is crucial because the uniform dispersion of the photocatalyst directly affects the formaldehyde removal effect of the final product.
[0084] S300, put artificial stone aggregate, zeolite powder, activated alumina and filler into a high-speed mixer for dry mixing. After dry mixing, add photocatalyst nano titanium dioxide dispersion and water reducer for wet mixing. Subsequently, add cement and auxiliary cementitious materials and continue to stir until a uniform mixture is formed. Finally, add toughening agent for the final stirring to ensure that the material has uniform moisture and reaches the characteristics suitable for compression molding.
[0085] S400, spread a PET film on the bottom of the molding die, and evenly spread the mixture on the PET film. Place the mold in the molding equipment, and perform high-frequency vibration pressing and molding under vacuum. During the pressing process, the vacuum degree is -0.095MPa, the press holding time is 120 to 180 seconds, and the press pressure is 12 to 16MPa.
[0086] S500, the formed artificial stone board is sent to the curing box for primary curing, and cured for 24 hours in an environment with a temperature of 20-40℃ and a humidity of ≥95%. After the primary curing is completed, demoulding is carried out, and then secondary curing is carried out to ensure that the cement-based board is fully reacted and cured.
[0087] S600, after the maintenance is completed, the finishing process is carried out, including thickness determination, grinding, polishing and protection, to meet the needs of different application scenarios.
[0088] Using the material portions described in the above embodiment, the corresponding formaldehyde-removing inorganic artificial stone was prepared according to the above method for preparing formaldehyde-removing inorganic artificial stone, and the degradation efficiency was tested experimentally. The results are shown in Table 1:
[0089] Table 1
[0090]
[0091] It can be seen from Table 1 that the formaldehyde removal rates of Example 1, Example 2 and Example 3 are 88.7%, 92.1% and 94.4% respectively, which shows that the inorganic artificial stone with the addition of photocatalyst nano-titanium dioxide, activated alumina and zeolite powder has a significant formaldehyde removal effect.
[0092] Furthermore, the formaldehyde removal rate of Comparative Example 1 (without photocatalyst nano-titanium dioxide) is only 20.3%, which clearly shows the key role of photocatalyst nano-titanium dioxide in the formaldehyde degradation process.
[0093] Furthermore, the formaldehyde removal rate of Comparative Example 2 (containing only photocatalyst nano-titanium dioxide, without activated alumina and zeolite) was 70.2%, which was lower than that of the embodiment, indicating that activated alumina and zeolite powder can enhance the adsorption effect of harmful gases, thereby enhancing the degradation efficiency of photocatalyst nano-titanium dioxide on formaldehyde.
[0094] Furthermore, compared with Example 2, in Example 3, the ratio of activated alumina and zeolite powder increased, and the removal rate also increased accordingly, which indicates that the formaldehyde removal efficiency can be further improved by optimizing the material ratio.
[0095] Furthermore, compared with Example 2 and Example 3, Example 1 has a relatively low removal rate due to a smaller amount of photocatalyst nano-titanium dioxide, which may indicate that within a certain range, increasing the amount of photocatalyst nano-titanium dioxide can improve the removal efficiency of formaldehyde.
[0096] Furthermore, although the data does not provide the effects of environmental factors such as light intensity and temperature on formaldehyde removal, the catalytic efficiency of photocatalysts is generally affected by these factors. Therefore, in practical applications, these environmental factors may need to be considered to optimize product performance.
[0097] Furthermore, the data in the table only provide the results of a single test, while the long-term performance and stability of the material need to be considered in actual application. Future research can focus on whether the formaldehyde removal efficiency of these materials will decrease during long-term use.
[0098] Furthermore, based on these data, it can be foreseen that this formaldehyde-removing inorganic artificial stone has broad application potential in the fields of interior decoration, furniture manufacturing, air purification, etc., especially in hospitals, schools and other places with high requirements for indoor air quality.
[0099] Furthermore, since the photocatalyst nano titanium dioxide, activated alumina and zeolite powder used are all non-toxic or low-toxic substances, the formaldehyde-removing inorganic artificial stone has good safety and environmental protection.
[0100] Furthermore, the present invention uses industrial tailings and construction solid waste in material selection, and the production of such materials has a lower cost, which helps to improve the market competitiveness of the product.
[0101] It should be understood that, although the steps in the flowchart of the accompanying drawings are displayed in sequence as indicated by the arrows, these steps are not necessarily executed in sequence in the order indicated by the arrows. Unless otherwise specified herein, there is no strict order restriction on the execution of these steps, and they can be executed in other orders. Moreover, at least a part of the steps in the flowchart of the accompanying drawings may include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be executed in turn or alternately with other steps or at least a part of the sub-steps or stages of other steps.
[0102] The above description is only a partial implementation method of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application. These improvements and modifications should also be regarded as the scope of protection of the present application.
Claims
1. A formaldehyde-removing inorganic artificial stone, characterized in that: The invention comprises the following raw materials in parts by weight: 20-30 parts of cement, 5-15 parts of auxiliary cementitious materials, 40-50 parts of construction solid waste, 10-20 parts of industrial tailings, 1-2 parts of photocatalyst, 2-4 parts of activated alumina, 1-3 parts of zeolite powder, 1-2 parts of water reducer, 1-2 parts of water and 3-6 parts of toughening agent. The preparation method of single-chip vacuum high-frequency vibration molding of photocatalyst nano titanium dioxide can effectively improve the strength, toughness and formaldehyde degradation rate of inorganic artificial stone.
2. The formaldehyde-removing inorganic artificial stone according to claim 1, characterized in that: The construction solid waste includes recycled concrete after crushing and screening. The particle size range and proportion of the construction solid waste include: 10 to 16 parts of 9.5 to 16 mm, 8 to 12 parts of 4.75 to 9.5 mm, 5 to 10 parts of 2.36 to 4.75 mm, 5 to 10 parts of 0.075 to 2.36 mm, and 5 to 10 parts of 0 to 0.075 mm.
3. The formaldehyde-removing inorganic artificial stone according to claim 1, characterized in that: The industrial tailings include one of copper tailings, lithium tailings or tungsten tailings. The particle size range and proportion of the industrial tailings include: 5 to 10 parts of 0.075 to 2.36 mm particle size and 10 to 15 parts of 0 to 0.075 mm particle size.
4. The formaldehyde-removing inorganic artificial stone according to claim 1, wherein the photocatalyst comprises nano-titanium dioxide with a particle size of 20 to 50 nm.
5. The formaldehyde-removing inorganic artificial stone according to claim 1, characterized in that: The specific surface area of the activated alumina is 200 to 300 m 2 / g, and the pore diameter of the zeolite powder is 0.3-1 nm.
6. The formaldehyde-removing inorganic artificial stone according to any one of claims 1 to 5, characterized in that: The auxiliary cementitious material includes metakaolin or bentonite; the water reducer includes a polycarboxylic acid water reducer; and the toughening agent includes styrene-butadiene emulsion or styrene-acrylic emulsion.
7. A method for preparing formaldehyde-free inorganic artificial stone, characterized in that: include: S100, uniformly dispersing the photocatalyst nano-titanium dioxide in water using an ultrasonic disperser to obtain a photocatalyst nano-titanium dioxide dispersion; S200, putting artificial stone aggregate, zeolite powder, activated alumina and filler into a high-speed mixer for dry mixing, then adding the photocatalyst nano titanium dioxide dispersion and admixture for wet mixing, adding cement and auxiliary cementitious material and continuing to stir, and finally adding toughening agent and continuing to stir, and after the stirring is completed, obtaining an artificial stone mixture with uniform moisture and suitable for compression molding properties; S300, laying a PET film on the bottom of the molding mold, evenly spreading the artificial stone mixture on the PET film, placing it in a molding device and vibrating and pressing it at high frequency under a vacuum state to obtain a molded artificial stone; S400, placing the formed artificial stone into a mold and then sending it into a curing box for primary curing, demoulding after the curing is completed, and continuing secondary curing after the demoulding is completed to ensure that the cement-based board is fully reacted and cured to reach a processable degree; S500, performing a finishing process to obtain the final formaldehyde-free inorganic artificial stone.
8. The method for preparing a formaldehyde-removing inorganic artificial stone according to claim 7, characterized in that: The total stirring time in step S200 is 5 to 10 minutes.
9. The method for preparing a formaldehyde-removing inorganic artificial stone according to claim 7, characterized in that: The vacuum degree of the pressing process in step S300 is -0.095 MPa, the holding time is 120 to 180 seconds, and the pressure is 12 to 16 MPa.
10. The method for preparing a formaldehyde-removing inorganic artificial stone according to claim 7, characterized in that: In the step S400, the first curing time is 24 hours, the temperature is 20-40° C., and the humidity is ≥95%. The second curing time is 14-28 days, the temperature is 20-40° C., and the humidity is ≥95%.
Citation Information
Patent Citations
Method for preparing doped nanometer titanium oxide photocatalyst
CN101301606A
Composite air purificant containing nanometer mineral matters and preparation method thereof
CN101780288A
Mildew-proof antibacterial inorganic artificial stone and preparation method thereof
CN117756453A
Tailing light-transmitting inorganic artificial stone and preparation method thereof
CN117886557A
Cited By
Photocatalyst functionalized inorganic artificial stone and preparation method thereof
CN122212813A